PHYSICAL CHANGES OF ANDALIMAN (ZANTHOXYLUM ACANTHOPODIUM DC.) IN PACKAGING DURING LOW-TEMPERATURE STORAGE - David Septian Sumanto Marpaung; Raizummi Fil'aini; Amna Citra Fahrani; Dwi Cahyani; Ayu Oshin Yap Sinaga (AGROINTEK, 2019)
Zanthoxylum acanthopodium, locally known as Andaliman, is exotic spices which grown in North Sumatera. Several investigation shown that the special taste and aroma comes from pericarp of Andaliman. However, the pericarp of Andaliman is easily degraded. The proper postharvest handling of Andaliman is necessary to preserve fresh Andaliman for long time. Previously, Andaliman has been preserved in packaging under room temperature storage. Further investigation of Andaliman preservation in packaging under low temperature storage would help reduces the postharvest losses. In this study, the physical changes of Andaliman in various packaging under low-temperature storage were observed. The results shown that within 2 days, the pericarp of Andaliman in paper packaging was shrunk, similarly found in control without packaging. Meanwhile, the pericarp of Andaliman in aluminum foil and PP plastic were found normal in day 3. This result indicated that in low-temperature, Andaliman in Aluminum foil was recommended for best postharvest handling.